Propagação in vitro e determinação do número cromossômico de Myrsine coriacea (Sw.) R.Br. ex Roem. & Schult. - Spadeto, Micheli Sossai (2015)
In vitro tissue culture techniques can generate subsidies for the propagation and germplasm maintenance of forest species of interest such as Myrsine coriacea (Sw.) R. Br. Ex Roem. & Schult. Primulaceae). This species has been high